2023
DOI: 10.3389/fimmu.2023.1057702
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anti-tumor efficacy of immune checkpoint blockade by alpha-TEA

Abstract: Cancer immunotherapy such as anti-PD-1/anti-PD-L1 immune checkpoint blockade (ICB) can provide significant clinical benefit in patients with advanced malignancies. However, most patients eventually develop progressive disease, thus necessitating additional therapeutic options. We have developed a novel agent, a-TEA-LS, that selectively induces tumor cell death while sparing healthy tissues, leading to increased activation of tumor-reactive T cells and tumor regression. In the current study, we explored the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Alpha‐tocopheryloxyacetic specifically causes tumor cell death while preserving healthy tissues. The study revealed that the combined therapy of alpha‐tocopheryloxyacetic and PD‐1 resulted in improved survival as well as reduced tumor size (86%), compared with 13% in the IgG group, 27% in the alpha‐tocopheryloxyacetic group and 17% in the PD‐1 group of control 42 . Moreover, recent work showed that the stimulator of interferon genes (STING) pathway introduces a new approach of biodegradable nanoparticles (NP1 and NP2) using a PC7A‐based polymer to encapsulate chemotherapeutic platinum complexes.…”
Section: Immunotherapiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Alpha‐tocopheryloxyacetic specifically causes tumor cell death while preserving healthy tissues. The study revealed that the combined therapy of alpha‐tocopheryloxyacetic and PD‐1 resulted in improved survival as well as reduced tumor size (86%), compared with 13% in the IgG group, 27% in the alpha‐tocopheryloxyacetic group and 17% in the PD‐1 group of control 42 . Moreover, recent work showed that the stimulator of interferon genes (STING) pathway introduces a new approach of biodegradable nanoparticles (NP1 and NP2) using a PC7A‐based polymer to encapsulate chemotherapeutic platinum complexes.…”
Section: Immunotherapiesmentioning
confidence: 98%
“…The study revealed that the combined therapy of alphatocopheryloxyacetic and PD-1 resulted in improved survival as well as reduced tumor size (86%), compared with 13% in the IgG group, 27% in the alphatocopheryloxyacetic group and 17% in the PD-1 group of control. 42 Moreover, recent work showed that the stimulator of interferon genes (STING) pathway introduces a new approach of biodegradable nanoparticles (NP1 and NP2) using a PC7A-based polymer to encapsulate chemotherapeutic platinum complexes. These nanoparticles are designed to enhance chemotherapy and immunotherapy through the activation of the STING pathway involving both DNA fragmentation/cyclic GMP-AMP synthase activation and PC7A binding.…”
Section: Programmed Cell Death Proteinmentioning
confidence: 99%